Biogenic Amines and Neuromodulation of Animal Behavior, 2nd Edition - Brian H. Smith (Frontiers Research Topics, 2018)
Since Erspamer and Boretti, 1951 first described the biogenic amine octopamine in the octopus salivary gland as a molecule with "adrenaline-like" action, decades of extensive studies demonstrated the important role octopamine and its precursor tyramine play in invertebrate physiology and behavior. This book contains the latest original research papers on tyramine/octopamine and their receptors in different neuronal and non-neuronal circuits of insects. Additonally, this book elucidates in detail the latest research on the function of other biogenic amines and their receptors, such as dopamine and serotonin in insects and mice. The reviews in this book summarize the most recent research on the role of biogenic amines in insect antennae, synaptic development, and behavioral modulation by spontaneous dopamine release in Drosophila. Finally, one perspective paper discusses the evolution of social behavior and biogenic amines. We recommend this book for all scholars interested in the latest advanced research on the role of biogenic amines in animal behavior. ITS dedicates the topic to her teacher, Plotnikova Svetlana Ivanovna (1922-2013).